Low Levels Of Physical Activity Are Associated With Cognitive Decline, Depressive Symptoms And Mobility Impairments In Older Adults Enrolled In A Health Insurance Plan - Henrique Souza Barros de Oliveira; Helena Cristina Buffalo; Isabella Ferlini Cieri; Laura Nicolau Nassif; Victória Maria Aguiar Fonai; Maria Elisa Gonzalez Manso (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVE: To verify the association of sociodemographic and clinical variables to different levels of physical activity in older adults enrolled in a health insurance plan in Brazil. METHODS: A quantitative cross-sectional study was conducted on a sample of 361 older adults enrolled in a health insurance plan in the city of São Paulo, SP, Brazil. Levels of physical activity were measured using the International Physical Activity Questionnaire (IPAQ), which has been translated, adapted and validated for use in Brazilian geriatric populations. Sociodemographic characteristics, functional capacity for activities of daily living, cognitive function, depressive symptoms, risk of falls, self-perceived health and nutritional status were also evaluated. Results were analyzed using descriptive methods followed by ANOVA and Chi-Square tests. When homogeneity of variances was violated, the Brown-Forsythe test was used, followed by Dunnett's test for multiple comparisons. RESULTS: Low levels of physical activity were reported by 63.3% of participants, with only 5.6% practicing vigorous physical activity. In this sample, variables such as positive self-perceived health (p = 0.032), adequate sleep without medication (p = 0.020) and independence for activities of daily living (p < 0.001) were positively associated with higher levels of physical activity. Advanced age (p < 0.001), cognitive decline (p < 0.001), depressive symptoms (p < 0.001) and mobility impairments (p < 0.001) were associated with low levels of physical activity. CONCLUSION: Demographic and clinical variables displayed positive and negative associations with different levels of physical activity in older adults receiving health insurance plans.